Development of an Assessment to Measure Science Process Skills for the Interaction of Living Things with Their Environment in Junior High School - oktavia, della (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
This study aims to develop an assessment to measure science process skills in the interaction of living things with their environment. The research method used is a research and development method consisting of 8 steps, namely research and initial information collection, planning, initial product format development, small-scale trials, product revisions, initial trials, and final products. The trial subjects in this research and development are exper subjects, namely assessment experts, material experts and linguists, as well as the subjects of class VII SMPN students in Bengkulu City as product users. Data were analyzed descriptively qualitatively and quantitatively. Feasibility assessment by three validator experts developed on the assessment aspect of 89%, material aspect of 93%, and language aspect of 93%, overall was declared very feasible with an average of 92%. This shows that the assessment of science process skills to measure science process skills is stated to be very suitable to be used to measure the level of students' science process skills. The assessment developed to measure Science Process Skills (KPS) is the science assessment, where in the development of the science assessment it uses formative assessment because this assessment is given to every lesson and can be carried out on sub-subjects or each subject. In the development of this formative assessment, multiple choice tests were developed.